Analisis Sektor Unggulan Kabupaten Oku Timur Terhadap Pertumbuhan Ekonomi di Provinsi Sumatera Selatan - Ismayanti, Nanda Aulia (Universitas Negeri Surabaya, 2023)
The purpose of this study was to identify the leading sectors in Ogan Komering Regency, East Ulu City Government. The secondary data used is from the Central Bureau of Statistics (BPS) for the identification basis sector with the Location Quotient (LQ) for the 2018-2022 period. This analysis focuses on the basic sectors and basic employment that determine the competitive region. The results of the Location Quotient (LQ) analysis of Ogan Komering Ulu district which have the highest potential for leading sectors among regencies/cities in South Sumatra Province are the Agriculture, Forestry and Fisheries sectors, the Wholesale and Retail Trade sector, Car and Motorcycle Repairs, the Accommodation Provision sector. and Food and Beverages, Real Estate sector, Education Services sector, Health and Social Activities sector, and Other Services sector.